Quantitative measurement of transthyretin mistargeting by proximity labeling and parallel reaction monitoring - Lyu, Ziqi; Genereux, Joseph C. (Frontiers in Chemical Biology, 2023)
Introduction: Proximity labeling is a powerful approach for characterizing subcellular proteomes. We recently demonstrated that proximity labeling can be used to identify mistrafficking of secretory proteins, such as occurs during pre-emptive quality control (pre-QC) following endoplasmic reticulum (ER) stress. This assay depends on protein quantification by immunoblotting and densitometry, which sometimes suffers from poor sensitivity. Methods: Here, we integrate parallel reaction monitoring (PRM) mass spectrometry to enable a more quantitative platform and assess how chemical ER stressors impact pre-QC of the model secretory protein transthyretin in HEK293T cells. Results and Discussion: We find that some drug treatments affect labeling efficiency, which can be controlled for by normalizing to APEX2 autolabeling. While some chemical ER stress inducers including Brefeldin A and thapsigargin induce pre-QC, tunicamycin and dithiothreitol do not, indicating ER stress alone is not sufficient. This finding contrasts with the canonical model of pre-QC induction, and establishes the utility of our platform.